2014
DOI: 10.1016/j.cryobiol.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Different concentrations of cysteamine and ergothioneine improve microscopic and oxidative parameters in ram semen frozen with a soybean lecithin extender

Abstract: The aim of this study was to evaluate the effects of ergothioneine and cysteamine as antioxidant supplements in a soybean lecithin extender for freezing ram semen. Twenty-four ejaculates were collected from four rams and diluted with extenders (1.5% soybean lecithin, 7% glycerol) containing no supplements (control) and cysteamine or ergothioneine (2, 4, 6 or 8mM). Motility by CASA, viability, plasma membrane functionality (HOS test), total abnormality, lipid peroxidation, glutathione peroxidase (GPx) activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 54 publications
4
21
0
3
Order By: Relevance
“…However, the feasibility and the quality of the produced ovine embryos are lower than for other species (Romao et al, 2013).This is mainly because ram spermatozoa are sensitive to the conditions of lowtemperature anabiosis and freezing (Sabev et al, 2006). Although semen possesses an antioxidant system, cryopreservation increases the intensity of lipid peroxidation of spermatozoa and their activity is affected (Najafi et al, 2014). Previous results showed that supplementation with antioxidants such as cysteamine, ergothioneine, vitamin E analogue, Trolox, catalase, and superoxide dismutase mimetic agent reduces lipid peroxidation and H 2 O 2 generation (Forouzanfar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the feasibility and the quality of the produced ovine embryos are lower than for other species (Romao et al, 2013).This is mainly because ram spermatozoa are sensitive to the conditions of lowtemperature anabiosis and freezing (Sabev et al, 2006). Although semen possesses an antioxidant system, cryopreservation increases the intensity of lipid peroxidation of spermatozoa and their activity is affected (Najafi et al, 2014). Previous results showed that supplementation with antioxidants such as cysteamine, ergothioneine, vitamin E analogue, Trolox, catalase, and superoxide dismutase mimetic agent reduces lipid peroxidation and H 2 O 2 generation (Forouzanfar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the antioxidant activity of polyphenols is more effective and less toxic than vitamins E and C. However, various factors, such as method of administration, dose, and structure of phenolic compounds, affect their activities (Silva et al, 2012). For example, antioxidants might have negative effects owing to excessive scavenging of free radicals, possibly by altering their physiological levels (Najafi et al, 2014). As shown in the current study, viability, motility and fertility of spermatozoa decreased significantly when higher concentrations of polyphenol quercetin (≥20 µg/mL) were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto se ve reflejado en la reducción de la movilidad, la viabilidad y la capacidad fecundante de dichas células (Najafi et al 2014). Sin embargo, los espermatozoides de asno han demostrado ser resistentes a los procesos de refrigeración y criopreservación, al mantener características adecuadas de calidad seminal (Vilés-López, 2013).…”
Section: Introductionunclassified
“…Semen cryopreservation has allowed specific opportunities for conservation of genetic resources through sperm banks, guarantee of a constant commercial supply of semen, and collaboration in breed improvement programs by artificial insemination (Bucak et al, 2007;Masoudi et al, 2017). Semen cryopreservation may lead to oxidative, chemical and physical damages on sperm membrane leading to reduction of sperm viability and fertility (Evans et al, 1987;Watson, 2000;Emamverdi et al, 2014;Najafi et al, 2014a;Sarıözkan et al, 2015). Freezing process mostly leads to loss of motility, acrosomal and plasma membrane functionality of spermatozoa (Tuncer et al, 2011;Najafi et al, 2013;Shahverdi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%